Biomechanical Aspects of Shoulder and Hip Articulations: A Comparison of Two Ball and Socket Joints - Jaffar, Dr. Akram Abood; Abass, Dr.Sadiq Jaffar; Ismael, Mustafa Qusay (Al-Khwarizmi Engineering Journal, 2017)
The shoulder and hip joints though essentially both are ball and socket joints, show structural variability to serve functional needs. This study aims at revealing some of the structural and functional properties of each of the two joints regarding the factors that contribute to the stability of any joint in the body, namely: bone, ligament, and muscle.